Characterization of walnut JrWOX11 and its overexpression provide insights into adventitious root formation and development and abiotic stress tolerance - Chang, Yingying; Song, Xiaobo; Li, Mingjun; Zhang, Qixiang; Zhang, Pu; Lei, Xiashuo; Pei, Dong (Frontiers in Plant Science, 2022)
Adventitious root (AR) formation is a critical developmental process in vegetative propagation through cuttings in some plants, primarily woody species. WUSCHEL-RELATED HOMEOBOX GENE 11 (WOX11) functions in AR formation in rice, Arabidopsis, and easy-to-root tree poplar. However, in difficult-to-root trees, the regulation of WOX11 during AR formation is poor. In this study, JrWOX11 gene was isolated from walnut and heterologous expressed in ‘84K’ poplar. The results showed JrWOX11 contained a similar structure and sequence to the homologous genes in rice, Arabidopsis, and poplar, but had different numbers and types of motifs and cis-elements. In addition, JrWOX11 expression was induced by PEG and NaCl stresses. Over-expression of JrWOX11 in poplar promoted root initiation, and significantly increased ARs number, lateral roots (LRs) number, and root hair (RH) length. Furthermore, the aboveground biomass was notablely increased under NaCl and PEG treatments in transgenic plants. When removed NaCl and PEG, the survival rate, the aerial shoot development and de nove root organogenesis were also markedly enhanced in transgenic shoot cuttings. The collective results could provide valuable information for revealing the differences between JrWOX11 and the homologous genes in rice, Arabidopsis, and poplar, and support the critical role of JrWOX11 in AR formation and salt and osmotic acclimation.